PANASONIC ACCELERATES DVD-RAM ADOPTION FOR UNIX/LINUX (CD Computing News, 2003)
For key small business applications, companies such as Objective Data Storage have chosen the powerful combination of DVD-RAM/DVD-R/ DVD-RW to deliver data management software to their customers operating on the UNIX/Linux platforms. DVD-RAM is not only fast, but it can handle large volumes of data on one 9.4GB DVD with rewriteability to approximately 100,000 times. In addition, thanks to advanced defect management and the power behind UNIX/Linux, users can rely on speedy, worry-free recording when archiving and burning data. Ultimately, users will be able to increase efficiency and accessibility in the workplace, and interact with mission-critical applications easier; all to enhance the user experience and increase ROI. The unique benefits of DVD-RAM over other formats add a new robustness to interacting with media and data via the UNIX/Linux platforms. DVD-RAM media offers users the benefits of defect management, on-disc editing and mixed file formats accessibility on one disc. In addition, the OEM MULTI Drive offers near universal media compatibility, allowing UNIX/Linux users the capability of archiving and burning media files to DVD-R and DVD-RW. Luminex develops distinctive data storage products that tackle the complex challenges of storing, archiving, distributing and protecting data. Complemented by quality customer service, Luminex's innovative products create real value for our customers. The Data|WARE(TM) product family simplifies CD and DVD creation for small to large businesses in finance, healthcare, prepress, government and education. Luminex's Virtual|BLUE(TM) line of parallel channel and ESCON emulators links IBM and plug-compatible mainframes with UNIX and Microsoft(R) systems, resulting in improved operations and economics for large data centers. Founded in 1994, Luminex is privately held and headquartered in Riverside, California, with additional offices in San Diego, California, and Beaverton, Oregon. Data|WARE and Virtual|BLUE products are available directly from Luminex and through selected partners worldwide. For more information about Luminex, email info@luminex.com or call 909/ 781-4100.